Establishing a Baseline: Evidence-Supported State Laws to Advance Stroke Care. (March 2020) - Gilchrist, Siobhan; Sloan, Arielle A.; Bhuiya, Aunima R.; Taylor, Lauren N.; Shantharam, Sharada S.; Barbero, Colleen; Fulmer, Erika B.
Abstract : Objective: Approximately 800 000 strokes occur annually in the United States. Stroke systems of care policies addressing prehospital and in-hospital care have been proposed to improve access to time-sensitive, lifesaving treatments for stroke. Policy surveillance of stroke systems of care laws supported by best available evidence could reveal potential strengths and weaknesses in how stroke care delivery is regulated across the nation. Design: This study linked the results of an early evidence assessment of 15 stroke systems of care policy interventions supported by best available evidence to a legal data set of the body of law in effect on January 1, 2018, for the 50 states and Washington, District of Columbia. Results: As of January 1, 2018, 39 states addressed 1 or more aspects of prehospital or in-hospital stroke care in law; 36 recognized at least 1 type of stroke center. Thirty states recognizing stroke centers also had evidence-supported prehospital policy interventions authorized in law. Four states authorized 10 or more of 15 evidence-supported policy interventions. Some combinations of prehospital and in-hospital policy interventions were more prevalent than other combinations. Conclusion: The analysis revealed that many states had a stroke regulatory infrastructure for in-hospital care that is supported by best available evidence. However, there are gaps in how state law integrates evidence-supported prehospital and in-hospital care that warrant further study. This study provides a baseline for ongoing policy surveillance and serves as a basis for subsequent stroke systems of care policy implementation and policy impact studies. Abstract : Supplemental Digital Content is Available in the Text.